HUBUNGAN POLA MAKAN, STRES KERJA, DAN MINUMAN TIDAK SEHAT DENGAN PENYAKIT DISPEPSIA DI WILAYAH KERJA PUSKESMAS LOA IPUH TENGGARONG KABUPATEN KUTAI KARTANEGARA TAHUN 2016 - Ilham Rahmatullah (Universitas Widya Gama Mahakam Samarinda, 2017)
Dyspepsia have clinical symptoms consist of pain or discomfort around the pit of the stomach so that the usual interfere with daily activities, both for teens and adults. Some risk factors that cause dyspepsia syndrome is a change in lifestyle, diet and unhealthy habits such as excessive cigarette smoking, excessive drinking, drinking beverages containing caffeine and drink soda.The study design used is analytic, with the design of case control. The research sample of 60 respondents where there were 30 cases and 30 controls with purposive sampliong technique. Data analysis using Chi Square test with a degree of error ?=5%.Statistical analysis showed no relationship between diet and dyspepsia with the value (? = 0.004 <? = 0.05), there is a relationship of work stress with dyspepsia with the value (? = 0,000 <? = 0.05), there is a relationship with the fizzy drinks dyspepsia (? = 0.035 <? = 0.05) and the relationship of caffeinated beverages with dyspepsia (? = 0.019 <? = 0.05) in Puskesmas Loa Ipuh Tenggarong. It can be concluded that diet, stress, work and drink unhealthy relationship with the incidence of dyspepsia disease in Puskesmas Loa Ipuh Tenggarong. Suggested attention to a regular diet, minimization stres, and reduce unhealthy drinking habits such as drinking carbonated beverages, and drinking beverages that can berkefein excessive risk of disease dyspepsia.